SYNTHESIS AND CHARACTERIZATION OF NOVEL SUBSTITUTED-1-(4-SUBSTITUTED BENZYL)-1H-INDOLO (2, 3-B) QUINOXALINE N-BENZYL INDOLE-2,3-DIONE MOIETIES - Gupta, Anil Kumar; Sharma, Manoj (Journal of Biomedical and Pharmaceutical Research, 2016)
Indole and its derivatives have occupied a unique place in the chemistry of nitrogen heterocyclic compounds. The indole derivatives were known for their dying properties. Hetero cyclic compounds represent an important class of biological molecules. The hetero cyclic molecules which posses indole, thiazole and tetrazole moieties exhibit wide range of biological activities. Indoles are one of the most important alkaloids molecules found extensively in biological systems, which play vital role in many of the biochemical process. Various novel Schiff bases derivatives were synthesized by a chain of reactions. Substituted isonitroso acetanilide were synthesized from substituted aniline and then further substituted-indole-2,3 dione (isatin) subsequently synthesized from substituted isonitroso acetanilide and finally yield different substituted-1-(4-substituted benzyl)-1H-indolo(2,3-b) quinoxaline N-benzyl indole-2,3-dione. All the synthesized compounds were identified by various methods and finally characterized by spectral analysis (IR, MS and NMR). Elemental analysis was also performed. Physical characteristics of Bromo-1-(4-methyl benzyl)-1H-indolo (2,3-b) quinoxaline N-benzyl indole-2,3-dione (compound QX5) was brownish solid; Yield: 80±4.14; Mol. Formula: C22H16N3Br, Mol.Wt: 402.26; Melting Point: 192 -194°C, Rf values: 0.62±0.16 Maximum wave length (λmax) in nm284; FTIR Spectra (KBr, cm-1): 3054-CH stretching (aromatic); 2919-CH stretching (aliphatic); 2847-CH stretching (aliphatic); 1607-C-N stretching; 1H-NMR (DMSO, δppm)– 8.65-7.12-15H, Ar H, 5.67-2H, N-CH2, 2.28-3H, CH3; 13C NMR-145.68-21.16; MS Spectra-402.28 and Physical characteristics of chloro-1-(4-methyl benzyl)-1H-indolo (2,3-b) quinoxaline N-benzyl indole-2,3-dione (compound QX4) was brownish solid Yield: 80±3.94; Mol. Formula: C22H16ClN3 Mol. Wt: 357.82; Melting Point: 193-196°C, Rf values: 0.58±0.12, Maximum wave length (λmax) in nm was 284; FTIR Spectra (KBr, cm-1): 3056-CH stretching (aromatic); 2916-CH stretching (aliphatic); 2844-CH stretching (aliphatic); 1614 -C-N stretching; 1H-NMR (DMSO, δppm)– 8.52-7.1611H, Ar-H, 5.71-2H, N-CH2, 2.36- 3H, CH3; 13C NMR-145.84-21.16; MS Spectra-357.83; CHN analysis- C%73.59 (73.84) H%3.23 (4.51) N%67.01 (11.75). Key words: Isatin, Schiff bases, Quinoxaline N-benzyl indole-2,3-dione